2003
DOI: 10.1097/00024382-200304000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Macrophage Inflammatory Chemokine-2 and Keratinocyte-Derived Chemokine on Hemorrhage-Induced Neutrophil Priming for Lung Inflammation: Assessment by Adoptive Cells Transfer in Mice

Abstract: Prior studies have shown that hemorrhage (Hem) can serve as a priming stimulus for acute lung injury (ALI) triggered by subsequent septic challenge (cecal ligation and puncture, CLP). Furthermore, we have reported that in vivo antibody neutralization of the chemokines, macrophage inflammatory chemokine-2 (MIP-2) and keratinocyte-derived chemokine (KC), immediately after Hem appears to differentially effect the onset of ALI. However, although we hypothesize that this is due to divergent effects of MIP-2 and KC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
108
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(117 citation statements)
references
References 29 publications
8
108
0
1
Order By: Relevance
“…In addition, levels of LIX and MIP-2 in ankles and hearts were unaltered in the KC Ϫ/Ϫ tissues, demonstrating a lack of compensatory changes during KC deficiency. Our results are in agreement with other studies suggesting that, despite apparent functional redundancy in vitro, in vivo these chemokines are under differentially regulated control, as illustrated by distinct tissue expression profiles, and likely have unique biological functions (4,17,32,44). Although functional redundancy is likely to exist under certain conditions in vivo, neutrophil recruitment and subsequent disease development during murine Lyme borreliosis appear to be mediated primarily via the KC/CXCR2 axis.…”
Section: Figsupporting
confidence: 91%
“…In addition, levels of LIX and MIP-2 in ankles and hearts were unaltered in the KC Ϫ/Ϫ tissues, demonstrating a lack of compensatory changes during KC deficiency. Our results are in agreement with other studies suggesting that, despite apparent functional redundancy in vitro, in vivo these chemokines are under differentially regulated control, as illustrated by distinct tissue expression profiles, and likely have unique biological functions (4,17,32,44). Although functional redundancy is likely to exist under certain conditions in vivo, neutrophil recruitment and subsequent disease development during murine Lyme borreliosis appear to be mediated primarily via the KC/CXCR2 axis.…”
Section: Figsupporting
confidence: 91%
“…Chemokines keratinocyte derivedchemokine (KC) and macrophage inflammatory protein-2 (MIP-2) both have been shown to participate in the pathogenesis of lung injury (36,37). The mRNA levels of KC and MIP-2 increased by 748-and 1415-fold, respectively, in the vehicle as compared with the sham (Figures 6A, B).…”
Section: Aicar Suppresses Lung Inflammation and Neutrophil Infiltratimentioning
confidence: 99%
“…25,27 Protein C activation is further diminished by protease cleavage of thrombomodulin (TM) as well as by a direct transcriptional down regulation of TM by circulating TNF-and IL-6. 28 Protein C stores are also depleted by an 23 accelerated conversion to activated protein C (aPC), degradation by protein C inhibitor (PCI), and impaired hepatic biosynthesis, all of which contribute to a state of protein C and aPC depletion in sepsis. 25 Mesters has reported that the depletion of protein C (and reduction of activated protein C plasma levels) precedes the onset of any sepsis by an average of 12 hours.…”
Section: Discussionmentioning
confidence: 99%
“…For mortality analysis, patients surviving to hospital discharge were assumed to still be alive. Secondary outcome measures were also recorded for 28-day ventilator-free days, acute lung injury (American-European consensus conference definition) 21 , VAP and acute renal injury (Acute Dialysis Quality Initiative consensus conference definition) 23 and blood transfusions required in the first 24 hours. Depleters were defined as having a slope more negative than the median during both time periods.…”
Section: Data Collection Outcome Measuresmentioning
confidence: 99%